Indonesia Diplomacy in Protecting the Rights of Indonesian Migrant Domestic Workers in Malaysia (2017-2022) - Novia, Hana; Djelantik, Sukawarsini (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2024)
This research aims to discuss the diplomatic efforts made by the Indonesian government to protect Indonesian Migrant Workers (PMI) in the domestic sector in Malaysia, where the majority of PMI are undocumented. In this case, the Indonesian Embassy in Kuala Lumpur is the representative of the Republic of Indonesia in Malaysia, which provides services and protection for Indonesian Citizens (Indonesian citizens) who stay in Malaysia, including human rights and migrant worker rights that every worker must have. This research will use qualitative methods with data collection techniques from observation, interviews, participation, and literature study originating from books, journals, articles, official reports, and online news. This research implements the track one diplomacy, negotiations, and international migration concept. The findings of this study show that the Indonesian government is making diplomatic efforts with Malaysia to provide maximum protection for PMI in the domestic sector of Malaysia. One of the ways the government provides PMI protection is through lengthy negotiations with Malaysia, which eventually resulted in a Memorandum of Understanding (MoU) on the Placement and Protection of Indonesian Migrant Domestic Workers in Malaysia in April 2022. Keywords: Track One Diplomacy, Indonesian Migrant Workers, Protection of Human Rights, Workers Rights